Impairments in balance and mobility identify delirium in patients with comorbid dementia. (15th October 2018) - Gual, Neus; Richardson, Sarah J.; Davis, Daniel H. J.; Bellelli, Giuseppe; Hasemann, Wolfgang; Meagher, David; Kreisel, Stefan H.; MacLullich, Alasdair M. J.; Cerejeira, Joaquim; Inzitari, Marco; Morandi, Alessandro
ABSTRACT: Diagnosing delirium superimposed on dementia (DSD) remains challenging because of a lack of specific tools, though motor dysfunction in delirium has been relatively under-explored. This study aimed to use dysfunction in balance and mobility (with the Hierarchical Assessment of Balance And Mobility: HABAM) to identify DSD. This is a cross-sectional multicenter study, recruiting consecutive patients ≥70 years admitted to five acute or rehabilitation hospitals in Ireland, Italy, Portugal, and Switzerland. Delirium was diagnosed using DSM-5 criteria; dementia was determined by the Mini-Mental State Examination and the Questionnaire of Cognitive Decline in the Elderly. HABAM score was recorded at admission. Out of 114 patients (mean age ± SD = 82 ± 7; 54% female), dementia alone was present in 24.6% ( n = 28), delirium alone in 18.4% ( n = 21) and DSD in 27.2% ( n = 31). Patients with DSD had a mean HABAM score 7 points greater than those with dementia alone (19.8 ± 8.7 vs 12.5 ± 9.5; p < 0.001); 70% of participants with DSD were correctly identified using the HABAM at a cut off of 22 (sensitivity 61%, specificity 79%, AUC = 0.76). Individuals with delirium have worse motor function than those without delirium, even in the context of comorbid dementia. Measuring motor function using the HABAM in older people at admission may help to diagnose DSD.